A self-directed learning intervention for radiographers rating mammographic breast density. Issue 4 (November 2017) - Ekpo, E.U.; Hogg, P.; Wasike, E.; McEntee, M.F.
Abstract: Purpose: Subjective methods of mammographic breast density (MBD) assessment are prone to inter-reader variability. This work aims to assess the impact of a short self-directed, experiential learning intervention on radiographers' reproducibility of MBD assessment. Method: The study used two sets of images (test and learning intervention) containing left craniocaudal and left mediolateral oblique views. The test set had MBD ratings from Volpara™ and radiologists using the fourth edition Breast Imaging and Data Systems (BI-RADS ® ). Seven radiographers rated the MBD of the test set before and after a self-directed learning intervention using the percentage descriptors in the fourth edition BI-RADS ® Atlas. The inter-reader agreement, the agreement between radiographers and Volpara™ as well as radiologists, was assessed using a Weighted Kappa (кw ). Results: Overall, radiographers' inter-reader agreement (кw ) was substantial (0.79; 95% CI: 0.70–0.87) before the intervention and almost perfect (0.84; 95% CI: 0.77–0.90) after the intervention. Before the intervention, radiographers demonstrated fair agreement with radiologists (0.24; 95% CI: −0.46–0.61) and Volpara™ (0.24; 95% CI: −0.41–0.59). A fair but slightly improved agreement was also observed between radiographers and radiologists (0.31; 95% CI: −0.33–0.64) as well as Volpara™ (0.28; 95% CI: −0.34–0.61) after the intervention. Conclusion: Findings demonstrate that a short duration self-directed, experiential learning intervention reduces inter-reader differences in MBD classification, but has a negligible impact on improving the agreement between inexperienced and expert readers. Highlights: Radiographers' MBD rating show fair agreement with radiologists and Volpara™. Experiential learning intervention improved reproducibility of MBD classification. Enhanced MBD rating training may be required to develop a standard fit for practice.